[Jespersen Tree] (1973)
Jespersen Tree, on Dexter Lawn, dedicated to Senator Chris Jespersen, an advocate for Cal Poly. In the background is the Agricultural Education (aka Ag Ed or Household Arts) Building, one of the first three buildings at Cal Poly, designed by William Weeks. It was demolished in September 1973, in this photo you can see the words "Save Me" on the roof, part of an unsuccessful student drive to save it. Proper spelling of the family name is 'Jespersen'; it is commonly misspelled 'Jesperson'.